High sodium diet converts renal proteoglycans into pro-inflammatory mediators in rats. - Ryanne S Hijmans; Pragyi Shrestha; Kwaku A Sarpong; Saleh Yazdani; Rana El Masri; Wilhelmina H A de Jong; Gerjan Navis; Romain R Vivès; Jacob van den Born (PLoS ONE, 2017)
High dietary sodium aggravates renal disease by affecting blood pressure and by its recently shown pro-inflammatory and pro-fibrotic effects. Moreover, pro-inflammatory modification of renal heparan sulfate (HS) can induce tissue remodeling. We aim to investigate if high sodium intake in normotensive rats converts renal HS into a pro-inflammatory phenotype, able to bind more sodium and orchestrate inflammation, fibrosis and lymphangiogenesis.Wistar rats received a normal diet for 4 weeks, or 8% NaCl diet for 2 or 4 weeks. Blood pressure was monitored, and plasma, urine and tissue collected. Tissue sodium was measured by flame spectroscopy. Renal HS and tubulo-interstitial remodeling were studied by biochemical, immunohistochemical and qRT-PCR approaches.High sodium rats showed a transient increase in blood pressure (week 1; p<0.01) and increased sodium excretion (p<0.05) at 2 and 4 weeks compared to controls. Tubulo-interstitial T-cells, myofibroblasts and mRNA levels of VCAM1, TGF-β1 and collagen type III significantly increased after 4 weeks (all p<0.05). There was a trend for increased macrophage infiltration and lymphangiogenesis (both p = 0.07). Despite increased dermal sodium over time (p<0.05), renal concentrations remained stable. Renal HS of high sodium rats showed increased sulfation (p = 0.05), increased L-selectin binding to HS (p<0,05), and a reduction of sulfation-sensitive anti-HS mAbs JM403 (p<0.001) and 10E4 (p<0.01). Hyaluronan expression increased under high salt conditions (p<0.01) without significant changes in the chondroitin sulfate proteoglycan versican. Statistical analyses showed that sodium-induced tissue remodeling responses partly correlated with observed HS changes.We show that high salt intake by healthy normotensive rats convert renal HS into high sulfated pro-inflammatory glycans involved in tissue remodeling events, but not in increased sodium storage.